(untitled) (Bangladesh Journal of Medical Biochemistry, 2018)
Gestational diabetes mellitus (GDM) is characterized by glucose intolerance during pregnancy. GDM is associated with an increased incidence of congenital abnormalities usually aggravated by maternal magnesium deficiency. Magnesium is one of the essential trace elements for normal embryogenesis and foetal growth and its deficiency increases mortality and morbidity rate of mothers, embryos and neonates. The present study was undertaken to evaluate the association of serum magnesium with GDM in second and third trimester of pregnancy. This case-control study was conducted in Mymensingh Medical College Hospital during the period from July 2013 to June 2014 to evaluate the association of serum magnesium with GDM in Bangladeshi women. A total of 172 subjects were recruited in this study; among them eighty six women with GDM were selected as case (Group-I) and eighty six healthy pregnant women were taken as control (Group- II). The cases again were subdivided as Group Ia and Ib at second and third trimester respectively. Controls also were subdivided as Group IIa and IIb at second and third trimester respectively. Student’s unpaired ’t’ test was used to compare the data between groups. For analytical purpose 95% confidence limit (p<0.05) was taken as level of significance. Serum magnesium level was significantly decreased in cases compared to that of controls. It was significantly lowered (p<0.001) in cases Gr-Ia (1.3884±0.255 mg/dl) than controls Gr-IIa (1.6651±0.304 mg/dl) at second trimester. The result was also significantly (p<0.001) lowered when compared between cases Gr-Ib (0.9349±0.145 mg/dl) and controls Gr-IIb (1.6674±0.308 mg/dl) at third trimester. The study shows that serum magnesium level is decreased in pregnancy with GDM. So estimation of serum magnesium level may be done in every GDM cases to reduce the incidence of magnesium related complications by timely intervention. Bangladesh J Med Biochem 2016; 9(2): 59-62